1993
DOI: 10.1161/01.res.73.2.360
|View full text |Cite
|
Sign up to set email alerts
|

Sequence elements required for transcriptional activity of the human myoglobin promoter in intact myocardium.

Abstract: To define sequence elements required for myoglobin gene transcription in the intact heart, we examined the expression of a reporter gene under the control of a 380-bp upstream segment (-373 to +7) from the human myoglobin gene in transgenic mouse embryos and after gene transfer into left ventricular myocardium of adult rats. This proximal upstream region was sufficient to direct expression of luciferase selectively in cardiac and skeletal muscle of mouse embryos and to recapitulate the pattern of expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…A myoglobin promoter segment truncated to nucleotides −373 to +7 (Mb380) was sufficient for muscle-specific expression in prior experiments (Devlin et al 1989;Bassel-Duby et al 1993;Grayson et al 1995) and was responsive to calcineurin stimulation in our current studies (Fig. 3A).…”
Section: Calcineurin-stimulated Transactivation Of Slowfiber-specificsupporting
confidence: 57%
See 1 more Smart Citation
“…A myoglobin promoter segment truncated to nucleotides −373 to +7 (Mb380) was sufficient for muscle-specific expression in prior experiments (Devlin et al 1989;Bassel-Duby et al 1993;Grayson et al 1995) and was responsive to calcineurin stimulation in our current studies (Fig. 3A).…”
Section: Calcineurin-stimulated Transactivation Of Slowfiber-specificsupporting
confidence: 57%
“…1). Previously, we defined two conserved upstream response elements within the myoglobin promoter, both of which are required for transcriptional activity in skeletal myotubes or cardiac myocytes (Devlin et al 1989;Bassel-Duby et al 1993;Grayson et al 1995Grayson et al , 1998. These CCAC and A/T elements represent binding sites for Sp1 and MEF2 proteins, respectively, and function synergistically in muscle-specific gene regulation (Grayson et al 1995(Grayson et al , 1998.…”
Section: Calcineurin-stimulated Transactivation Of Slowfiber-specificmentioning
confidence: 99%
“…Plasmid DNA (50 g) containing segments of the human myoglobin gene promoter (19) was introduced into the soleus or extensor digitorum longus (EDL) muscle 3 days after injury. Muscles were harvested 10 days after bupivacaine injection and assayed for reporter activity.…”
Section: Methodsmentioning
confidence: 99%
“…Transcriptional Activity of the Human Myoglobin Gene Promoter in Regenerating Muscles of the Rat-Previous studies of the human myoglobin gene promoter in cultured cells (14,18) and following somatic cell gene transfer into the hearts of intact rats (19) suggested that important transcriptional regulatory elements reside in the proximal 5Ј flanking region. Here we determined that a segment of the human myoglobin gene extending from Ϫ373 to ϩ7 base pairs relative to the transcriptional initiation site is sufficient to direct muscle-specific expression of a luciferase reporter gene in a pattern that mirrors that of the endogenous myoglobin gene.…”
Section: Stringent Regulation Of Myoglobin Protein Expression In Dif-mentioning
confidence: 99%
See 1 more Smart Citation